Atividade antibiofilme e propriedades físicas de cimentos endodônticos associados à amoxicilina, pó tri-antibiótico e diclofenaco sódico - Freitas, Rafaela Pignatti de (2018)
The endodontic treatment aims to promote the maximum elimination of bacteria from the root canal system, however, the persistence of these microorganisms, either by previous endodontic treatment or by reinfection in the canal through microleakage, favors treatment failure. Enterococcus faecalis is the bacterial species isolated from root canals with the highest prevalence in secondary infections. It is of concern to the dental surgeon that the root canal system be thoroughly cleaned during the bio-mechanical preparation and a complete sealing with sealing cements. In order to inhibit bacterial growth, it is extremely important that the obturator materials possess antimicrobial activity so that in the filling they can confine and, if possible, eliminate the microorganisms that have adapted to the new environment. The addition of antibiotics to endodontic cements has been proposed in order to enhance the antibacterial action of the sealing materials. Therefore, the objective of this work was to evaluate the antibiofilm efficacy of the AH Plus, Sealer 26 and Endofill sealants, associated to amoxicillin, tri-antibiotic powder and diclofenac sodium, when submitted to biofilm formation by E. faecalis strain ATCC 29212. Blocks of each pure cement were made and associated with the medications with approximately 5 mm of diameter by 2 mm of thickness. For 21 days, the blocks of the cements were subjected to a culture of E. faecalis ATCC 29212. At the end of the biofilm formation, the blocks were examined by laser scanning confocal microscopy at 40X magnification in order to determine the percentage of bacterial viability. Three specimens were photographed in each group and 4 photos were taken per specimen, totaling 12 photos per group. The images were analyzed by bioImage_L software. The evaluation of the physical properties of the cements and the time of prey of the pure cements and associated with the drugs were evaluated according to ANSI / ADA standards. The association of Endofill cement associated with tri-antibiotic powder revealed better antimicrobial performance (1.011% viability) on E. faecalis biofilm ATCC 29212, followed by the combination of AH Plus with the anti-inflammatory diclofenac sodium (5.64% viability). In relation to the physical tests all the cements and their associations presented yield results within the values specified by ISO 6876 of 2012. In relation to the holding time the results were evaluated in minutes. In the test of initial prey time the pure cement Endofill was the one that presented lower average (60 min) and the association of Sealer 26 with the antibiotic amoxicillin major (922 min). In the test of final prey time the pure cement Endofill presented lower value (130 min) and cement AH Plus associated with diclofenac sodium indicated the highest values (1605 min). Therefore, as combinations of Endofill + tri-antibiotic powder and AH Plus + diclofenac sodium presented better results in relation to antimicrobial activity and adequate flow values. However, the holding time of all pure and associated cements presented values for the variation allowed by the standard 57 ANSI/ADA. Thus, future studies are needed, mainly, regarding solubility and biological behavior, these mixtures.